Zollinger-Ellison Syndrome - review - Metelski, Jakub; Metelska, Aleksandra; Sereda, Dominika; Nieścior, Hubert; Szwed, Monika (Journal of Education, Health and Sport, 2022)
Introduction and purpose Zollinger-Ellison syndrome (ZES) is a constellation of symptoms that includes gastric ulcer, gastroesophageal reflux disease (GERD), and chronic diarrhea. They are caused by the presence of gastrinoma, which is a neuroendocrine tumor that secretes gastrin. Gastrinoma is most often found in the duodenum and pancreas. ZES occurs sporadically in about 80% of cases, while in 20-25% it is a component of multiple endocrine neoplasms (MEN1). It is malignant in 60-90% of cases. The aim of the study is to present the typical clinical course of ZES, the diagnostic path and current therapeutic recommendations. Description of the state of knowledge ZES is present in about 0.1% -1% of patients with peptic ulcer disease. The direct cause of symptoms in patients with ZES is excessive gastric secretion stimulated by ectopic gastrin. Excess gastric acid damages the gastric mucosa and small intestine and disrupts the transport of fats, leading to the development of diarrhea. Other common symptoms include abdominal pain, nausea, or more rarely severe complications of GERD or peptic ulcer disease. Diagnostics include measurement of fasting serum gastrin, measurement of gastric pH, and assessment of basal gastric acid production. Summary In pharmacological treatment, proton pump inhibitors (PPIs) are the first-line drugs to control excessive gastric acid secretion in patients with ZES. Other therapeutic options include histamine receptor antagonists or somatostatin analogues. Surgical intervention remains the only possible causal treatment. In the case of sporadic ZES routine exploratory laparotomy with curative intent is recommended. In the group of patients with coexisting MEN-1 syndrome, surgical intervention is reserved for patients with tumors> 2 cm.